Bandwidth Behavior of Closely Spaced Aperture-Coupled Reflectarrays - F. Venneri; S. Costanzo; G. Di Massa (International Journal of Antennas and Propagation)
The bandwidth features of reflectarray antennas are analyzed by examining in detail the phase errors due to the compensation mechanism for spatial phase delays. A bandwidth estimation rule is defined, taking into account the combined effects due to the overall antenna geometry and the frequency response of the single reflectarray element. An aperture-coupled reflectarray configuration with reduced interelement spacing is considered as broadband solution for the implementation of small reflectarrays. A 20 GHz aperture-coupled element is synthesized for the design of a 12𝜆 diameter reflectarray, showing a simulated 1 dB gain bandwidth of 23%.